Mad Money. - Nelson, Scott (National Interest)
The article offers information about the popularity of blockchain and cryptocurrencies in 2018, and discusses how digital assets are designed to work as a medium of exchange that uses strong cryptography to secure financial transactions, control the creation of additional units, and verify the transfer of assets. Topics discussed include increase in the Capital formation through so-called initial coin offerings (icos);emergence of cryptocurrency as a functioning measure of value; and the U.S. official's concerns of money laundering due to blockchain and cryptocurrencies.